Comparative analyses of the old and modern surnames of Poltava region (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The classification of the old and modern surnames were performed in the work with taking into account double motivation. The specific of both periods is shown.
Keywords: surname; motivation; semantic; derivation